Acrophialophora jodhpurensis: an endophytic plant growth promoting fungus with biocontrol effect against Alternaria alternata - Daroodi, Zoha; Taheri, Parissa; Tarighi, Saeed (Frontiers in Plant Science, 2022)
In this study, efficiency of the endophytic fungal isolate Msh5 was evaluated on promoting tomato plant growth and controlling Alternaria alternata, the causal agent of early blight in tomatoes. Morphological and molecular (ITS and tub2 sequences) analyses revealed that the fungal isolate, Msh5, was Acrophialophora jodhpurensis (Chaetomium jodhpurense Lodha). This beneficial fungus was capable of producing indole-3-acetic acid (IAA), urease, siderophore, extracellular enzymes, and solubilized phosphate. Under laboratory conditions, the Msh5 isolate of A. jodhpurensis inhibited A. alternata growth in dual culture, volatile and non-volatile metabolites assays. The supernatant of this endophytic fungus was capable of reducing spore germination and altering the hyphal structure of A. alternata and the spores produced germ tubes showed vacuolization and abnormal structure compared to the control. Also, the effect of A. jodhpurensis on plant growth parameters (such as shoot and root weight and length) and suppressing A. alternata was investigated in vivo via seed inoculation with spores of A. jodhpurensis using 1% sugar, 0.5% carboxymethyl cellulose (CMC) or 0.5% molasses solution as stickers. Colonization of tomato roots by the endophytic fungus resulted in significant increasing plant growth parameters and reduction in the progress of the diseases caused by A. alternata compared to the controls. Among the different coating materials used as stickers, sugar was found to be the most effective for enhancing plant growth parameters and decreasing the disease progress. Therefore, A. jodhpurensis isolate Msh5 can be suggested as a potential biofertilizer and biocontrol agent for protecting tomato plants against A. alternata.